Penggunaan Media Pembelajaran Berbasis Android untuk Meningkatkan Hasil Belajar Kognitif Siswa - Putri, Dian Puspita Eka (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
This study aims to review the effectiveness of using android-based multimedia learning to improve achievement cognitive learning outcome of students. The research method is the analysis of field studies. The focus in this research is Multimedia which can influence cognitive learning outcomes of students. data obtained in this study from the literature and direct field observations. The research subjects were high school students in Yogyakarta. The result of analysis and discussion of research indicate that there is the influence of multimedia learning to increase student achievement, which is indicated by increasing post-test result than before not using multimedia learning. Posttest value is greater than pretest.